2012
DOI: 10.1074/jbc.m111.310946
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of B Cell Receptor Signaling by Hematopoietic Progenitor Kinase 1 (HPK1)-mediated Phosphorylation and Ubiquitination of Activated B Cell Linker Protein (BLNK)

Abstract: Background: HPK1 is a hematopoiesis-specific Ste20-like serine/threonine kinase that suppresses immune responses and autoimmunity. Results: HPK1 knock-out B cells show loss of Thr-152 phosphorylation, 14-3-3 binding, and Lys-37/38/42-ubiquitination of BLNK. Conclusion: HPK1 attenuates BCR signaling via inducing phosphorylation and ubiquitination of BLNK.Significance: This is the first report of BLNK ubiquitination that is initiated by HPK1-induced phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…Interestingly, BLNK, also known as SLP-65, which in B cells has a function related to that of SLP-76 in T cells, is also regulated by 14-3-3. Thus, it was recently reported that hematopoietic progenitor kinase 1 (HPK1), by phosphorylating threonine 152 in BLNK, attenuates BCR-mediated activation, since 14-3-3 binding to T152 causes ubiquitination and degradation of BLNK (59). This also suggests that other components than Btk can contribute to the enhanced activation that we observed upon BV02 treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, BLNK, also known as SLP-65, which in B cells has a function related to that of SLP-76 in T cells, is also regulated by 14-3-3. Thus, it was recently reported that hematopoietic progenitor kinase 1 (HPK1), by phosphorylating threonine 152 in BLNK, attenuates BCR-mediated activation, since 14-3-3 binding to T152 causes ubiquitination and degradation of BLNK (59). This also suggests that other components than Btk can contribute to the enhanced activation that we observed upon BV02 treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Finally, other SLP-76 family adaptor proteins, including BLNK and CLNK, also interact with and activate HPK1. In fact, we note that HPK1 feedback induces BLNK phosphorylation and ubiquitination in B cells during B cell receptor signaling (30). A future study of the potential regulation of CLNK activation by HPK1-induced phosphorylation may lead to interesting findings.…”
Section: Hpk1-mediated Slp-76 Ubiquitinationmentioning
confidence: 99%
“…BCR signaling is tightly regulated, and elevated or sustained BCR signaling has been shown to be associated with autoimmunity (4). Attenuation of BCR signaling is mediated by various phosphatases and kinases, including SH2-containing inositol 5-phosphatase (SHIP-1) (5) and hematopoietic progenitor kinase 1 (HPK1) (6). SHIP-1 inhibits activation of phospholipase-Cγ2 (PLCγ2), Bruton's tyrosine kinase, and Akt by eliminating their membrane docking sites, consequently blocking their downstream signaling (5).…”
mentioning
confidence: 99%
“…SHIP deficiency causes hyperresponsiveness and impaired affinity maturation of B cells in germinal centers (GCs) (7). HPK1 inhibits BCR signaling by inducing phosphorylation and subsequent ubiquitination of B-cell linker protein (BLNK) (6), the key adaptor molecule of the BCR. HPK1 deficiency results in elevated levels of activated BLNK, MAP kinases, B-cell proliferation, and resultant susceptibility to induced autoimmunity (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation